A nanoclay-based 3D aerogel framework for flexible flame retardants. Issue 17 (22nd July 2022) - Xie, Weimin; Wang, Jie; Shang, Kaixuan; Chen, Hongyun; Tang, Aidong; Wu, Mingjie; Cui, Xun; Yang, Huaming
Abstract : A high-performance flexible flame-retardant CR/PA/PVA aerogel was obtained via employing cellulose-dispersed nanoclay as both 3D skeleton and antiflaming component and polyaniline and polyvinyl alcohol as flexibilizer and crosslinker, respectively. Abstract : The rational design and facile synthesis of flame-retardant aerogels featuring superior compressibility and favorable flexibility are crucial for green advanced buildings and soft decoration but remain challenging due to the general inaccessibility of both high flame retardancy and good flexibility. Herein, we report a facile route to crafting an emerging ternary crosslinked composite aerogel with an interpenetrating three-dimensional (3D) network structure via employing cellulose-dispersed nanoclay ( i.e., rectorite) (CR) as both a 3D skeleton and a flame-retardant component and organic polyaniline (PA) and polyvinyl alcohol (PVA) as a flexibilizer and a crosslinker, respectively. Specifically, a stable rectorite suspension is first prepared by introducing cellulose nanocrystals to alleviate the agglomeration of rectorite nanosheets. Subsequently, the in situ polymerization of PA on the surface of the obtained CR nanosheets and the addition of PVA lead to the formation of a ternary network aerogel (denoted as CR/PA/PVA). Impressively, the horizontal 3D structures and radial wave-shape layers of CR/PA/PVA ensure outstanding compression resilience, bendability, and foldability. Remarkably, CR nanosheets as a thermal and qualitative insulator significantly improve the peak heat release rate (as low as 8.3 kJ m −2 ) of CR/PA/PVA, outperforming most state-of-the-art flame-retardant products. As such, the rationally designed interpenetrating 3D network structured CR/PA/PVA offers a unique platform for developing high-performance flexible flame retardants.